Factors influencing the perceptions of Islamic finance researchers towards sukuk - Asalie, M. Imam (2019)
The aim of this research paper is to identify the determinates of Islamic finance researchers’ perceptions towards Sukuk-Waqf by measuring the following factors: awareness, religious obligation, and reputation. A set of questionnaires were designed to clarify the differences of perceptions towards Sukuk-Waqf. The goals of this study are to identify the variations of Islamic finance researchers’ perceptions based on the demographic factors such as gender, age, religion, educational level, reading of Islamic finance materials, and years of experience in the field of the Islamic finance industry. Also, to determine the relationship between (awareness, religious obligation, and reputation) and the perceptions of Islamic finance researchers towards Sukuk-Waqf. The study has targeted certain population which is the academicians and postgraduate students in Malaysia who are majoring their studies in the lore of Islamic finance. It employed a quantitative type of research using questionnaires and the sample comprised of 413 respondents. The study found three determinants to be significant in influencing the perceptions of Islamic finance researchers towards Sukuk-Waqf namely Awareness, Religious Obligation, and Reputation. Therefore, this study provided great contributions, implications and has recommended for Islamic Waqf planning institutions and Islamic financial institutions which offer Islamic financial instruments to improve Waqf operations.